SEXUALITY AND DISABILITY : SEX THERAPY AND REHABILITATION OF PEOPLE WITH SPINAL CORD - Cláudia Bortolozzi Maia, Ana (2011)
The paper presents a theoretical discussion about the relationship between sexuality and disability. Talks about the concepts of sexuality and disability as socially constructed and then argue the myths and prejudices that underpin the beliefs of an atypical sexuality when it comes to people with disabilities. Delves into the issue focusing on the person with spinal cord injury, pointing to possible limitations on the phases of sexual response and also important aspects of sex therapy and rehabilitation of this population.